CXCR4 expression enhances diffuse large B cell lymphoma dissemination and decreases patient survival. Issue 3 (11th December 2014) - Moreno, María José; Bosch, Rosa; Dieguez‐Gonzalez, Rebeca; Novelli, Silvana; Mozos, Ana; Gallardo, Alberto; Pavón, Miguel Ángel; Céspedes, María Virtudes; Grañena, Albert; Alcoceba, Miguel; Blanco, Oscar; Gonzalez‐Díaz, Marcos; et al.
Abstract The chemokine receptor CXCR4 has been implicated in the migration and trafficking of malignant B cells in several haematological malignancies. Over‐expression of CXCR4 has been identified in haematological tumours, but data concerning the role of this receptor in diffuse large B cell lymphoma (DLBCL) are lacking. CXCR4 is a marker of poor prognosis in various neoplasms, correlating with metastatic disease and decreased survival of patients. We studied CXCR4 involvement in cell migration in vitro and dissemination in vivo. We also evaluated the prognostic significance of CXCR4 in 94 biopsies of DLBCL patients. We observed that the level of expression of CXCR4 in DLBCL cell lines correlated positively with in vitro migration. Expression of the receptor was also associated with increased engraftment and dissemination, and decreased survival time in NOD/SCID mice. Furthermore, administration of a specific CXCR4 antagonist, AMD3100, decreased dissemination of DLBCL cells in a xenograft mouse model. In addition, we found that CXCR4 expression is an independent prognostic factor for shorter overall survival and progression‐free survival in DLBCL patients. These results show that CXCR4 mediates dissemination of DLBCL cells and define for the first time its value as an independent prognostic marker in DLBCL patients. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd